Protestant missionary children's lives, c.1870-1950: empire, religion and emotion - Morrison, Hugh Douglas (Studies in imperialism, 2024)
Protestant missionary children s historical lives are examined from the perspectives of parents, churches and children, to reveal complicated existences. This book takes a comparative approach across a range of settings, drawing on oral history, childhood history and histories of emotion. It extends scholarship into the mid-twentieth century